The Role of Parents in Building Children's Character in QS. As-Saffat verses 102-105: A Comparative Analysis of Tafsir al-Azhar and Tafsir Ibnu Katsir - Anggita Nabila Siagian; Hasyimsyah Nasution (JIA (Jurnal Ilmu Agama), 2025)
One of the factors contributing to the prevalence of juvenile delinquency is a lack of moral awareness in children. This occurs due to low parental supervision of children and the influence of their surroundings. This leads to the prevalence of promiscuity and a lack of control from the social environment of adolescents. The role of parents, especially fathers, is very influential in the development of children. A father's attitude greatly influences the character of the children he raises. In line with the message in the Qur'an, fathers greatly influence the character of their children, as in the stories of Prophet Ibrahim and Prophet Ismail, which are the focus of this study. This study aims to determine how the roles of fathers and mothers can influence the development of children's character, particularly the message contained in QS. As-Saffat verses 102-105. This study employs a qualitative approach with a literature review focused on Tafsir al-Azhar and Tafsir Ibnu Katsir. Since the primary objects of this study are the Qur’anic verses and the interpretations of these two scholars, the study uses the comparative exegesis method. The results indicate that Prophet Ibrahim, as the father of Prophet Ismail, played a significant role in shaping his son’s character. In relation to modern-day parents, it is important to emulate the story of Prophet Ibrahim and Prophet Ismail in child-rearing. The story recorded in QS. As-Saffat verses 102–105 teaches the importance of gentle communication, setting an example in faith, and shaping a child’s character through attitude, not just advice. In the face of modern challenges, this approach is relevant for building strong relationships and instilling moral and spiritual values in children. In raising his son, he instilled the fundamental principles of strong faith and obedience to Allah's commands. Additionally, patience and sincerity are key elements in navigating life.